The Power of Beauty filters: How Does It Impacts Body Image? - Nabila, Zurrotin; Hanim, Lailatul Muarofah (Universitas Muhammadiyah Sidoarjo, 2024)
Increasingly unrealistic beauty standards will result in the way a person and others view their bodies. This study aims to see the effect of the intensity of using beauty filters on body image in early adult Instagram users. This research was conducted on 275 women aged 18-25 years. The analysis used was simple linear regression test with the help of IBM SPSS Version 25 for Windows. The results showed a value of F = 5.530 with a significance of 0.019, meaning that there is a significant effect of the intensity of the use of Instagram beauty filters on body image.